Advantages and Disadvantages of Integrating AI Tools to English Language Teaching: Systematic Literature Review - Paraguas, Almira S. (JLE: Journal of Literate of English Education Study Program, 2025)
The integration of AI tools to English Language Teaching (ELT) has presented new opportunities, emerging as a potential tool for interactive and individualized learning. This review will explore the advantages and disadvantages of integrating AI tools to English Language Teaching by analyzing 50 peer-reviewed articles published between 2021 and 2025 from ERIC, JSTOR, SAGE Journals, and ScienceDirect databases. Through inclusion-exclusion criteria, 50 articles (25-Quantitative; 10 Qualitative; 15-Mixed-Method) were included for synthesis. The findings revealed that the advantages of integrating AI Tools in ELT are enhancing students’ learning experiences, improving writing abilities, increasing students’ motivation and engagement, and offering instant and personalized feedback. Academic integrity (plagiarism), inaccurate/generic responses, and over-reliance on AI tools are the disadvantages of integrating AI tools in ELT. AI tools offer numerous benefits that cater to individual student needs, learning styles and paces, fostering greater engagement and motivation. Despite promising advantages, the integration of AI in English Language Teaching presents several challenges. Teacher training and professional development are also crucial to ensure effective and ethical integration of AI in the classroom. Hence, the integration of AI tools to ELT emphasizes the significance of adopting innovative pedagogies, a student-centered approach, and certain ethical considerations.